Klasifikasi Kategori Buku Ilmu Agama Islam Menggunakan Metode Naive Bayes Dan Seleksi Fitur Information Gain - Panji Gemilang; Yuita Arum Sari; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Books that have important role for making the next generation of nation intelligent, creative, and critical. Special reading books on Islamic religion have various categories, for example categories of creed, morals, sirah, and so forth. Books about Islam and various categories that exist makes it difficult for people to find the desired book according to the category of books that you want to read. Thus this study seeks to classify Islamic religious book categories into 7 categories using the Naive Bayes Multinomial and feature selection Information Gain. The classification process starts from the preprocessing text, features selection by the Information Gain method, and classification using the method Multinomial Naive Bayes. Testing is acuration, precision, and recall with 2 scenarios, namely through the process of stemming and not through the process stemming also analysis the influence of threshold Information Gain. Displaying scenarios through stemming with a 50% feature selection has the best accuracy, precision, and recall results of 69%, 74%, and 69% by order. Based on testing algorithms can classify the categories of Islamic religious science books using the Naive Bayes Multinomial method and feature selection Information Gain